Functional socks using far-infrared radiating minerals and method for manufacturing the same
Patent Information
- Application Number
- KR1020260077783
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-04-29
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2046-04-29
Smart Images

Figure 112026052442919-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to functional socks using far-infrared radiation minerals and a method for manufacturing the same.
[0002] More specifically, the invention relates to a sock manufactured using a fiber having a patch attached that includes a far-infrared radiating mineral and an anion-generating mineral rich in rare earth elements, and a method for manufacturing the same. Background Technology
[0003] Functional clothing utilizing minerals is based on technology that imparts physical and chemical properties to textile materials by incorporating or coating them with specific inorganic substances. These mineral particles play a role in enhancing wearer comfort and hygiene through characteristics such as thermal conductivity, reflectivity, surface activity, and ion emission. In this process, since the manifestation of function depends heavily on particle size, dispersion state, and the method of bonding with the fiber, materials engineering design becomes a key element.
[0004] In terms of functionality, the most widely utilized fields are antibacterial and deodorizing effects, thermal regulation, and UV protection. Silver ions exhibit antibacterial effects by damaging bacterial cell membranes or inhibiting enzyme activity, which can be applied to sportswear or medical textiles. Additionally, some ceramic or mineral composites can help maintain body temperature by reflecting and re-emitting sunlight or body heat. UV protection also utilizes the scattering and absorption characteristics of mineral particles, with the concentration and distribution of the particles determining the blocking rate.
[0005] Far-infrared (FIR), frequently mentioned in relation to mineral-based functional fibers, generally refers to electromagnetic waves with wavelengths ranging from approximately 3 to 1000 μm and is closely related to thermal interactions with the human body and the surrounding environment. Some minerals may possess the characteristic of absorbing thermal energy and re-emitting it in the form of far-infrared rays, and mineral particles are introduced onto the surface or inside of fibers utilizing this property. However, since this is a radiation phenomenon induced by external energy rather than spontaneous emission, the actual degree of far-infrared function varies depending not only on the inherent properties of the material itself but also on the usage environment, temperature conditions, and particle distribution.
[0006] Theoretically, far-infrared rays can facilitate heat transfer by interacting with the vibrational and rotational energy states of molecules within a material, and in the human body, they can induce heat absorption at the skin surface and subtle thermal effects. These characteristics are associated with improved blood flow and muscle relaxation, and are sometimes presented as additional effects of functional clothing.
[0007] Consequently, the core value of mineral-based far-infrared functional clothing must be comprehensively considered in terms of the emissivity, thermal conductivity, dispersion stability within the fiber, and washing durability of the mineral particles. Accordingly, follow-up research is underway to quantitatively determine the correlation between far-infrared emission characteristics and the actual effects of human application, and to establish evaluation methods based on international standards, but no significant results have been reported.
[0008] One of the concepts often mentioned in relation to mineral-based functional fibers is the negative ion. Some minerals, particularly those with piezoelectric and thermoelectric properties such as tourmaline, can cause minute charge separation in response to external stimuli; it is suggested that they may interact with molecules in the air during this process to contribute to the formation of negative ions. Additionally, certain metal oxides or ceramic particles may exhibit the ability to emit or adsorb electrons through surface reactions.
[0009] To realize functions based on negative ion generation, the electrical properties of mineral particles, surface area, the method of immobilization within the fiber, and external stimulation conditions interact comprehensively. In subsequent research, it is important to quantify the amount of negative ions generated under actual wear conditions and objectively evaluate their impact on the human body and the environment. This will help reduce the discrepancy between functional claims and actual performance, leading to the development of reliable materials.
[0010] Meanwhile, mineral-based functional clothing requires consideration in terms of durability, safety, and environmental impact. If functional particles detach during the washing process, it can lead not only to performance degradation but also to the environmental release of fine particles. In particular, regarding silver nanoparticles, ongoing discussions regarding ecotoxicity alongside their antibacterial effects necessitate the development of immobilization technologies or alternative materials. Furthermore, as these are products that come into contact with the skin, an evaluation of biocompatibility and potential allergens is essential.
[0011] Based on these results, the inventors manufactured a viscous patch using a mineral with excellent far-infrared emissivity and confirmed that functional socks manufactured using a fiber to which the patch is attached exhibit excellent deodorizing and antibacterial effects. Through this, the present invention regarding functional socks using a far-infrared radiating mineral and a method for manufacturing the same was completed. Prior art literature
[0012] Korean Registered Patent Publication No. 10-1816394 The problem to be solved
[0013] The present invention aims to provide a functional sock made of a functional fiber comprising a far-infrared emitting patch.
[0014] The present invention also aims to provide a far-infrared emitting composition comprising urethane and a far-infrared generating mineral, wherein the far-infrared emitting composition comprises 75-85 wt% urethane, 5-9 wt% olivine, 2-4 wt% germanium, and 8-12 wt% apatite based on 100 wt% of the composition.
[0015] The present invention also comprises the steps of: preparing mineral powder by grinding urethane, a far-infrared emitting mineral, and an anion emitting mineral; preparing a mineral mixture by mixing the mineral powder with a binder composition; preparing a far-infrared emitting patch by molding the mineral mixture; attaching the far-infrared emitting patch to a fiber surface at intervals of 0.5 to 1.5 cm; and a post-treatment step of UV-curing the far-infrared emitting patch attached to the fiber surface. The method comprises the step of weaving socks using fibers that have undergone the above post-processing step, wherein the far-infrared radiating mineral comprises olivine, germanium, and apatite, and the negative ion radiating mineral comprises one or more selected from the group consisting of tourmaline, illite, barley stone, zeolite, and bioceramic, the mineral powder has an average particle size (D50) of 1 to 50 μm, the weight ratio of the mineral powder to the binder composition is 4:6 to 7:3, and the binder composition comprises, based on 100 wt% of the binder composition, 40 to 55 wt% urethane acrylate, 10 to 25 wt% isobornyl acrylate, 5 to 20 wt% hexanediol diacrylate, 5 to 12 wt% ester resin, and terpene phenol The purpose is to provide a method for manufacturing functional socks characterized by including 1 to 8 wt% of resin and 2 to 5 wt% of a photoinitiator.
[0016] The purposes of the present disclosure are not limited to those mentioned above, and other purposes and advantages of the present disclosure not mentioned may be understood from the following description and will be more clearly understood from the embodiments of the present disclosure. Furthermore, it will be readily apparent that the purposes and advantages of the present disclosure can be realized by the means and combinations thereof set forth in the claims. means of solving the problem
[0017] The present invention provides a functional sock made of a functional fiber comprising a far-infrared emitting patch.
[0018] The above far-infrared emitting patch is characterized by containing a far-infrared generating mineral.
[0019] The above far-infrared emitting mineral may be included in the form of a powder, and the mineral powder may be characterized by having an average particle size (D50) of 1 to 50 μm.
[0020] The above far-infrared emitting patch may be characterized by further including urethane.
[0021] The above far-infrared emitting mineral is characterized by containing rare earth elements.
[0022] The above far-infrared emitting mineral may be characterized by including olivine, germanium, and apatite.
[0023] The far-infrared emitting patch may be characterized by comprising 75-85 wt% urethane, 5-9 wt% olivine, 2-4 wt% germanium, and 8-12 wt% apatite, based on 100 wt% of the emitting patch.
[0024] The above rare earth elements may be characterized by including lanthanum (La) and yttrium (Y) elements.
[0025] The above rare earth elements may be characterized by further including one or more selected from the group consisting of Scandium (Sc), Cerium (Ce), Praseodymium (Pr), Neodymium (Nd), Samarium (Sm), Europium (Eu), Gadolinium (Gd), Dysprosium (Dy), Holmium (Ho), Erbium (Er), Thulium (Tm), Ytterbium (Yb), and Lutetium (Lu).
[0026] The above far-infrared emitting patch may be characterized by further including a reinforcing agent.
[0027] The reinforcing agent may be characterized by comprising one or more selected from the group consisting of silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), calcium oxide (CaO), iron oxide (Fe2O3), barium oxide (BaO), lead oxide (PbO), titanium dioxide (TiO2), sodium oxide (NaO2), potassium oxide (K2O), manganese (Mn), chromium (Cr), nickel (Ni), copper (Cu), zirconium (Zr), cobalt (Co), and vanadium (V).
[0028] The above reinforcing agent may be characterized by having a surface modified with fluoroalkylsilane (FAS) and mercaptosilane.
[0029] The above fluoroalkylsilane (FAS) and mercaptosilane may be characterized by being included in an amount of 1 to 8 parts by weight based on 100 parts by weight of the total reinforcing agent, preferably in an amount of 2 to 5 parts by weight.
[0030] The above fluoroalkylsilane (FAS) and mercaptosilane may be characterized by being included in a weight ratio of 1:0.5 to 1:2.
[0031] The above far-infrared emitting patch may be characterized by having a low amount of radon emission.
[0032] The above radon emission amount is 43~48 Bq / m³ 3 It may be characterized by the following.
[0033] The above far-infrared emitting patch may be characterized by further including negative ion-generating minerals.
[0034] The above-mentioned anion-generating mineral may be characterized by comprising one or more selected from the group consisting of tourmaline, illite, barley stone, zeolite, and bioceramic.
[0035] The above far-infrared emitting patch may further include a binder composition.
[0036] The weight ratio of the mineral powder and the binder composition may be 4:6 to 7:3.
[0037] The binder composition may be characterized by comprising, based on 100 wt% of the binder composition, 40-55 wt% of urethane acrylate, 10-25 wt% of isobornyl acrylate, 5-20 wt% of hexanediol diacrylate, 5-12 wt% of ester resin, 1-8 wt% of terpene phenol resin, and 2-5 wt% of a photoinitiator.
[0038] The above functional fiber may be characterized by comprising: a far-infrared emitting layer including a far-infrared emitting patch; and a heat radiating layer coupled to one side of the far-infrared emitting layer.
[0039] The above thermal radiation layer may be characterized by having a file loop structure that forms an air layer.
[0040] The above thermal radiation layer has a loop length in the range of 2 to 5 mm and 10 to 25 loop / cm 2 It may be characterized by having a range of loop densities.
[0041] The above thermal radiation layer may have a porosity in the range of 50 to 90%, and preferably may be characterized by having a porosity in the range of 60 to 80%.
[0042] The above heat-radiating layer may be characterized by including terry cloth and brushed fabric.
[0043] The above terry fabric and brushed fabric may be characterized by being mixed in a weight ratio of 1:0.4 to 1:0.8.
[0044] The above functional socks may be characterized by having an earthing function using conductive yarn.
[0045] The above conductive yarn may be characterized by including copper yarn, carbon yarn, silver-coated yarn, nickel-coated yarn, etc.
[0046] The present invention also provides a far-infrared emitting composition comprising urethane and a far-infrared generating mineral, wherein the far-infrared emitting composition comprises 75-85 wt% urethane, 5-9 wt% olivine, 2-4 wt% germanium, and 8-12 wt% apatite based on 100 wt% of the composition.
[0047] The above far-infrared emitting mineral is characterized by containing rare earth elements.
[0048] The above far-infrared emitting mineral may be characterized by including olivine, germanium, and apatite.
[0049] The above rare earth elements may be characterized by including lanthanum (La) and yttrium (Y) elements.
[0050] The above rare earth elements may be characterized by further including one or more selected from the group consisting of Scandium (Sc), Cerium (Ce), Praseodymium (Pr), Neodymium (Nd), Samarium (Sm), Europium (Eu), Gadolinium (Gd), Dysprosium (Dy), Holmium (Ho), Erbium (Er), Thulium (Tm), Ytterbium (Yb), and Lutetium (Lu).
[0051] The above far-infrared emitting composition may be characterized by further including a reinforcing agent.
[0052] The reinforcing agent may be characterized by comprising one or more selected from the group consisting of silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), calcium oxide (CaO), iron oxide (Fe2O3), barium oxide (BaO), lead oxide (PbO), titanium dioxide (TiO2), sodium oxide (NaO2), potassium oxide (K2O), manganese (Mn), chromium (Cr), nickel (Ni), copper (Cu), zirconium (Zr), cobalt (Co), and vanadium (V).
[0053] The above reinforcing agent may be characterized by having a surface modified with fluoroalkylsilane (FAS) and mercaptosilane.
[0054] The above fluoroalkylsilane (FAS) and mercaptosilane may be characterized by being included in an amount of 1 to 8 parts by weight based on 100 parts by weight of the total reinforcing agent, preferably in an amount of 2 to 5 parts by weight.
[0055] The above fluoroalkylsilane (FAS) and mercaptosilane may be characterized by being included in a weight ratio of 1:0.5 to 1:2.
[0056] The above far-infrared emitting patch may be characterized by further including negative ion-generating minerals.
[0057] The above-mentioned anion-generating mineral may be characterized by comprising one or more selected from the group consisting of tourmaline, illite, barley stone, zeolite, and bioceramic.
[0058] The above far-infrared emitting mineral may be included in the form of a powder, and the mineral powder may be characterized by having an average particle size (D50) of 1 to 50 μm.
[0059] The above far-infrared emitting composition may further include a binder composition.
[0060] The weight ratio of the mineral powder and the binder composition may be 4:6 to 7:3.
[0061] The binder composition may be characterized by comprising, based on 100 wt% of the binder composition, 40-55 wt% of urethane acrylate, 10-25 wt% of isobornyl acrylate, 5-20 wt% of hexanediol diacrylate, 5-12 wt% of ester resin, 1-8 wt% of terpene phenol resin, and 2-5 wt% of a photoinitiator.
[0062] The present invention also provides a method for manufacturing functional socks, comprising the steps of: grinding a far-infrared emitting mineral and a negative ion generating mineral to produce a mineral powder; mixing the mineral powder with a binder composition to produce a mineral mixture; molding the mineral mixture to produce a far-infrared emitting patch; attaching the far-infrared emitting patch to a fiber surface at intervals of 0.5 to 1.5 cm; applying a UV-curing coating to the far-infrared emitting patch attached to the fiber surface; and weaving socks using the fiber that has undergone the post-treatment step.
[0063] The above far-infrared emitting minerals may include olivine, germanium, and apatite.
[0064] The above anion-generating mineral may include one or more selected from the group consisting of tourmaline, illite, barley stone, zeolite, and bioceramic.
[0065] The above mineral powder may be characterized by having an average particle size (D50) of 1 to 50 μm.
[0066] The weight ratio of the mineral powder and the binder composition may be characterized as being 4:6 to 7:3.
[0067] The binder composition may be characterized by comprising, based on 100 wt% of the binder composition, 40-55 wt% of urethane acrylate, 10-25 wt% of isobornyl acrylate, 5-20 wt% of hexanediol diacrylate, 5-12 wt% of ester resin, 1-8 wt% of terpene phenol resin, and 2-5 wt% of a photoinitiator.
[0068] The step of manufacturing the above mineral powder may further include a step of grinding with additional reinforcing agent.
[0069] The reinforcing agent may be characterized by comprising one or more selected from the group consisting of silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), calcium oxide (CaO), iron oxide (Fe2O3), barium oxide (BaO), lead oxide (PbO), titanium dioxide (TiO2), sodium oxide (NaO2), potassium oxide (K2O), manganese (Mn), chromium (Cr), nickel (Ni), copper (Cu), zirconium (Zr), cobalt (Co), and vanadium (V).
[0070] The above reinforcing agent may be characterized by having a surface modified with fluoroalkylsilane (FAS) and mercaptosilane.
[0071] The above fluoroalkylsilane (FAS) and mercaptosilane may be characterized by being included in an amount of 1 to 8 parts by weight based on 100 parts by weight of the total reinforcing agent, preferably in an amount of 2 to 5 parts by weight.
[0072] The above fluoroalkylsilane (FAS) and mercaptosilane may be characterized by being included in a weight ratio of 1:0.5 to 1:2.
[0073] The step of weaving the above socks may further include the step of weaving the socks using fibers including a heat-radiating layer.
[0074] The above thermal radiation layer may be characterized by having a file loop structure that forms an air layer.
[0075] The above thermal radiation layer has a loop length in the range of 2 to 5 mm and 10 to 25 loop / cm 2 It may be characterized by having a range of loop densities.
[0076] The above thermal radiation layer may have a porosity in the range of 50 to 90%, and preferably may be characterized by having a porosity in the range of 60 to 80%.
[0077] The above heat-radiating layer may be characterized by including terry cloth and brushed fabric.
[0078] The above terry fabric and brushed fabric may be characterized by being mixed in a weight ratio of 1:0.4 to 1:0.8. Effects of the invention
[0079] The functional socks of the present invention emit far-infrared rays to exhibit an excellent deodorizing effect.
[0080] The functional socks of the present invention have the effect of exhibiting excellent far-infrared emissivity, radiation dose, and radiant energy.
[0081] The functional socks of the present invention further include a heat radiation layer, which has the effect of suppressing the external emission of far-infrared rays and heat. Brief explanation of the drawing
[0082] FIG. 1 shows a schematic diagram of a functional sock manufactured according to one embodiment of the present invention. FIG. 2 shows a schematic diagram of a far-infrared emitting patch attached to the inner surface of a functional sock that comes into contact with the sole, manufactured according to one embodiment of the present invention. FIG. 3 shows a functional sock manufactured according to one embodiment of the present invention. FIG. 4 shows a far-infrared emitting patch attached to the inner surface of a functional sock that comes into contact with the sole, manufactured according to one embodiment of the present invention. Figure 5 shows the antibacterial effect against E. coli of a functional sock manufactured according to one embodiment of the present invention. Figure 6 shows the antibacterial effect against Staphylococcus aureus of a functional sock manufactured according to one embodiment of the present invention. Specific details for implementing the invention
[0083] The present invention will be described in detail below.
[0084] The term 'far infrared radiation' used in this invention is generally defined as electromagnetic waves with a wavelength in the range of about 4 μm to 1,000 μm, and has a longer wavelength than visible light and is closely related to the thermal behavior of materials.
[0085] All objects emit radiant energy in proportion to their absolute temperature, and in particular, in the room temperature range (about 20–40°C), a significant portion of the emission spectrum is distributed in the far-infrared region. Due to this characteristic, far-infrared radiation is understood as a major component of thermal radiation beyond a simple optical concept, and its emission intensity and distribution are explained by Planck's radiation law and the Stefan-Boltzmann law.
[0086] Far infrared rays possess the characteristic of stimulating energy levels corresponding to molecular vibration and rotation during interactions with matter, and exhibit high absorption rates, particularly in materials containing moisture. Consequently, internal absorption and thermal conversion of far infrared rays predominate over surface reflection, which can contribute to uniformizing the temperature distribution within the material.
[0087] The term 'rare earth elements (REEs)' used in the present invention refers to a total of 17 elements, including 15 lanthanide elements from lanthanum (La, atomic number 57) to lutetium (Lu, atomic number 71) in the periodic table, plus scandium (Sc) and yttrium (Y), which have similar chemical properties.
[0088] These elements have the characteristic of filling electrons in the 4f orbitals in terms of electronic structure, and as a result, they exhibit similar chemical behavior. Rare earth elements are utilized as key materials in various advanced industries due to their excellent magnetic, optical, and catalytic properties.
[0089] The term 'pile loop structure' as used in this invention refers to a structure in which loop-shaped fiber loops are formed protruding from the surface of a fabric. This structure is formed by bonding additional pile yarn onto a ground fabric and is realized by controlling the pile yarn to remain in a loop shape during the weaving or knitting process.
[0090] Loops can be classified into uncut (loop pile) and cut (cut pile) states; maintaining a loop shape offers advantages in forming air layers along with an increased surface area. The key characteristics of the pile loop structure lie in porosity and bulkiness, which are determined by the height, density, and arrangement of the loops. Once loops are formed, air layers are trapped within and on the surface of the fabric; these air layers play a role in improving thermal insulation performance due to the low thermal conductivity of air.
[0091] As used in this specification, the term "comprising" is a term that does not exclude the existence or addition of items other than those mentioned.
[0092] In this specification, a numerical range indicated by the term 'to' represents a numerical range that includes the values listed before and after the term as a lower limit and an upper limit, respectively. Where multiple numerical values are disclosed as the upper and lower limits of an arbitrary numerical range, the numerical range disclosed in this specification may be understood as an arbitrary numerical range in which any one of the multiple lower limits and any one of the multiple upper limits are set as the lower limit and upper limit, respectively.
[0093] As used herein, the term 'and / or' is a term comprising each of the mentioned items and all combinations of one or more. Additionally, the singular form includes the plural form unless otherwise noted.
[0094] Terms or words used in this specification and claims should not be interpreted as being limited to their ordinary dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.
[0095] Therefore, it should be understood that the configurations described in the embodiments of this specification are merely the most preferred embodiments of the present invention and do not represent all of the technical ideas of the present invention, and that various equivalents and modifications that can replace them may exist at the time of filing this application.
[0096] The present invention will be explained in more detail below through examples and experimental examples. However, these examples and experimental examples are intended to illustrate the invention and the scope of the present invention is not limited to these experimental examples.
[0097] The present invention provides a functional sock (100) made of a functional fiber including a far-infrared emitting patch (200).
[0098] In one embodiment according to the present invention, the far-infrared emitting patch is characterized by including a far-infrared generating mineral.
[0099] In one embodiment according to the present invention, the far-infrared radiating mineral may be included in the form of a powder, and the mineral powder may be characterized by having an average particle size (D50) of 0.5 to 70 μm, preferably 1 to 50 μm.
[0100] In one embodiment according to the present invention, the far-infrared emitting patch may be characterized by further including urethane.
[0101] In one embodiment according to the present invention, the far-infrared generating mineral may be characterized by including rare earth elements.
[0102] In one embodiment according to the present invention, the far-infrared generating mineral may be characterized by including olivine, germanium, and apatite.
[0103] In one embodiment according to the present invention, the far-infrared emitting patch may be characterized by comprising 75-85 wt% urethane, 5-9 wt% olivine, 2-4 wt% germanium, and 8-12 wt% apatite, based on 100 wt% of the emitting patch.
[0104] In one embodiment according to the present invention, the rare earth element may be characterized by including lanthanum (La) element and yttrium (Y) element.
[0105] In one embodiment according to the present invention, the rare earth element may further comprise one or more elements selected from the group consisting of Scandium (Sc), Cerium (Ce), Praseodymium (Pr), Neodymium (Nd), Samarium (Sm), Europium (Eu), Gadolinium (Gd), Dysprosium (Dy), Holmium (Ho), Erbium (Er), Thulium (Tm), Ytterbium (Yb), and Lutetium (Lu).
[0106] In one embodiment according to the present invention, the far-infrared emitting patch may be characterized by further including a reinforcing agent.
[0107] In one embodiment according to the present invention, the reinforcing agent may be characterized by comprising one or more selected from the group consisting of silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), calcium oxide (CaO), iron oxide (Fe2O3), barium oxide (BaO), lead oxide (PbO), titanium dioxide (TiO2), sodium oxide (NaO2), potassium oxide (K2O), manganese (Mn), chromium (Cr), nickel (Ni), copper (Cu), zirconium (Zr), cobalt (Co), and vanadium (V).
[0108] In one embodiment according to the present invention, the reinforcing agent may be characterized by having a surface modified with fluoroalkylsilane (FAS) and mercaptosilane.
[0109] In one embodiment according to the present invention, the fluoroalkylsilane (FAS) and mercaptosilane may be characterized by being included in an amount of 1 to 8 parts by weight based on 100 parts by weight of the total reinforcing agent, preferably in an amount of 2 to 5 parts by weight.
[0110] In one embodiment according to the present invention, the fluoroalkylsilane (FAS) and mercaptosilane may be characterized by being included in a weight ratio of 1:0.5 to 1:2.
[0111] In one embodiment according to the present invention, the far-infrared emitting patch may be characterized by further including a negative ion generating mineral.
[0112] In one embodiment according to the present invention, the anion-generating mineral may be characterized by comprising one or more selected from the group consisting of tourmaline, illite, barley stone, zeolite, and bioceramic.
[0113] In one embodiment according to the present invention, the far-infrared emitting patch may further comprise a binder composition.
[0114] In one embodiment according to the present invention, the weight ratio of the mineral powder and the binder composition may be 4:6 to 7:3.
[0115] In one embodiment according to the present invention, the binder composition may be characterized by comprising, based on 100 wt% of the binder composition, 40 to 55 wt% of urethane acrylate, 10 to 25 wt% of isobornyl acrylate, 5 to 20 wt% of hexanediol diacrylate, 5 to 12 wt% of ester resin, 1 to 8 wt% of terpene phenol resin, and 2 to 5 wt% of a photoinitiator.
[0116] In one embodiment according to the present invention, the functional fiber may be characterized by comprising: a far-infrared emitting layer (110) including a far-infrared emitting patch; and a heat radiating layer (120) coupled to one side of the far-infrared emitting layer.
[0117] In one embodiment according to the present invention, the thermal radiation layer may be characterized by having a file loop structure that forms an air layer.
[0118] In one embodiment according to the present invention, the thermal radiation layer has a loop length in the range of 2 to 5 mm and 10 to 25 loop / cm 2 It may be characterized by having a range of loop densities.
[0119] In one embodiment according to the present invention, the thermal radiation layer may have a porosity in the range of 50 to 90%, and preferably may be characterized by having a porosity in the range of 60 to 80%.
[0120] In one embodiment according to the present invention, the heat-radiating layer may be characterized by including a terry cloth and a brushed fabric.
[0121] In one embodiment according to the present invention, the terry fabric and the brushed fabric may be characterized by being mixed in a weight ratio of 1:0.4 to 1:0.8.
[0122] The present invention will be explained in more detail below through embodiments such as those shown in FIGS. 1 to 4. However, these embodiments and experimental examples are intended to illustrate the present invention and the scope of the present invention is not limited to these experimental examples, nor are materials within the equivalent range excluded.
[0123] Example 1
[0124] Urethane resin and far-infrared emitting minerals were ground to produce a powder form. A polyurethane-based resin was used as the urethane resin, and olivine, germanium, and apatite were used as the far-infrared emitting minerals. The far-infrared emitting mineral must contain at least 0.009% of Lanthanum (La) and at least 0.004% of Yttrium (Y) out of 100% of the total rare earth element content, as determined by performing a compositional analysis of the candidate mineral; additionally, it must contain one or more elements selected from the group consisting of Scandium (Sc), Cerium (Ce), Praseodymium (Pr), Neodymium (Nd), Samarium (Sm), Europium (Eu), Gadolinium (Gd), Dysprosium (Dy), Holmium (Ho), Erbium (Er), Thulium (Tm), Ytterbium (Yb), and Lutetium (Lu). Selected to contain more than 0.0001%. The above urethane resin and far-infrared emitting mineral were used after being uniformly ground to an average particle size (D50) of 30 μm, and were composed to contain 80 wt% urethane, 7 wt% olivine, 3 wt% germanium, and 10 wt% apatite based on 100 wt% of the total powder.
[0125] A far-infrared emitting patch was manufactured by combining the above powder with a binder composition. The binder composition was prepared to have viscosity and was composed to include 50 wt% urethane acrylate, 18 wt% isobornyl acrylate, 14 wt% hexanediol diacrylate, 9 wt% ester resin, 6 wt% terpene phenol resin, and 3 wt% photoinitiator, based on 100 wt% of the binder composition. The above powder and the above binder composition were mixed and stirred, then molded into a circular shape with a diameter of 0.5 mm, cooled, and stored.
[0126] Subsequently, fibers for weaving socks were prepared, and far-infrared emitting patches manufactured by the above method were attached to the surface in contact with the sole of the foot at 1 cm intervals. After attachment, a UV curing coating at 385 nm was performed to prevent the patches from sticking to the sole of the foot. After complete curing, socks were woven using the same fibers.
[0127] Example 2
[0128] Urethane resin, far-infrared emitting minerals, and negative ion emitting minerals were ground to produce a powder form. Polyurethane-based resin was used as the urethane resin, and olivine, germanium, and apatite were used as the far-infrared emitting minerals. The far-infrared emitting mineral must contain at least 0.009% of Lanthanum (La) and at least 0.004% of Yttrium (Y) out of 100% of the total rare earth element content, as determined by performing a compositional analysis of the candidate mineral; additionally, it must contain one or more elements selected from the group consisting of Scandium (Sc), Cerium (Ce), Praseodymium (Pr), Neodymium (Nd), Samarium (Sm), Europium (Eu), Gadolinium (Gd), Dysprosium (Dy), Holmium (Ho), Erbium (Er), Thulium (Tm), Ytterbium (Yb), and Lutetium (Lu). We selected those containing more than 0.0001%.
[0129] Tourmaline, illite, and zeolite were used as anion-generating minerals. The urethane resin, far-infrared ray-generating mineral, and anion-generating mineral were uniformly ground to an average particle size (D50) of 30 μm and used. Based on 100 wt% of the total powder, the composition included 70 wt% urethane, 7 wt% olivine, 3 wt% germanium, 10 wt% apatite, 4 wt% tourmaline, 3 wt% illite, and 3 wt% zeolite.
[0130] Subsequently, a far-infrared emitting patch was manufactured and socks were woven using the same method as in Example 1 above.
[0131] Example 3
[0132] Urethane resin, far-infrared emitting minerals, negative ion emitting minerals, and reinforcing agents were ground to produce a powder form. Polyurethane-based resin was used as the urethane resin, and olivine, germanium, and apatite were used as the far-infrared emitting minerals. The far-infrared emitting mineral must contain at least 0.009% of Lanthanum (La) and at least 0.004% of Yttrium (Y) out of 100% of the total rare earth element content, as determined by performing a compositional analysis of the candidate mineral; additionally, it must contain one or more elements selected from the group consisting of Scandium (Sc), Cerium (Ce), Praseodymium (Pr), Neodymium (Nd), Samarium (Sm), Europium (Eu), Gadolinium (Gd), Dysprosium (Dy), Holmium (Ho), Erbium (Er), Thulium (Tm), Ytterbium (Yb), and Lutetium (Lu). We selected those containing more than 0.0001%.
[0133] Tourmaline, illite, and zeolite were used as anion-generating minerals. Metal oxides and single-element metals were mixed and used as reinforcing agents; although various types may be used, in this invention, silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), calcium oxide (CaO), iron oxide (Fe2O3), nickel (Ni), zirconium (Zr), cobalt (Co), and vanadium (V) were mixed and used. The above urethane resin, far-infrared generating mineral, negative ion generating mineral, and reinforcing agent were used after being uniformly ground to an average particle size (D50) of 30 μm, and based on 100 wt% of the total powder, it was composed to include 65 wt% urethane, 7 wt% olivine, 3 wt% germanium, 10 wt% apatite, 4 wt% tourmaline, 3 wt% illite, 3 wt% zeolite, 2 wt% silicon dioxide, 0.6 wt% aluminum oxide, 0.6 wt% magnesium oxide, 0.5 wt% calcium oxide, 0.4 wt% iron oxide, 0.3 wt% nickel, 0.3 wt% zirconium, 0.2 wt% cobalt, and 0.1 wt% vanadium.
[0134] Subsequently, a far-infrared emitting patch was manufactured and socks were woven using the same method as in Example 1 above.
[0135] Example 4
[0136] Urethane resin, far-infrared emitting minerals, negative ion emitting minerals, and reinforcing agents were ground to produce a powder form. Polyurethane-based resin was used as the urethane resin, and olivine, germanium, and apatite were used as the far-infrared emitting minerals. The far-infrared emitting mineral must contain at least 0.009% of Lanthanum (La) and at least 0.004% of Yttrium (Y) out of 100% of the total rare earth element content, as determined by performing a compositional analysis of the candidate mineral; additionally, it must contain one or more elements selected from the group consisting of Scandium (Sc), Cerium (Ce), Praseodymium (Pr), Neodymium (Nd), Samarium (Sm), Europium (Eu), Gadolinium (Gd), Dysprosium (Dy), Holmium (Ho), Erbium (Er), Thulium (Tm), Ytterbium (Yb), and Lutetium (Lu). Those containing more than 0.0001% were selected. Tourmaline, illite, and zeolite were used as anion-generating minerals.
[0137] As reinforcing agents, a mixture of metal oxides and single-element metals was used. Although various types may be used, in the present invention, a mixture of silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), calcium oxide (CaO), iron oxide (Fe2O3), nickel (Ni), zirconium (Zr), cobalt (Co), and vanadium (V) was used. The surface of the reinforcing agent was surface modified with fluoroalkylsilane (FAS) and mercaptosilane, and the fluoroalkylsilane (FAS) and mercaptosilane were included in a weight ratio of 1:1, with 4 parts by weight based on 100 parts by weight of the total reinforcing agent.
[0138] The above urethane resin, far-infrared generating mineral, negative ion generating mineral, and reinforcing agent were used after being uniformly ground to an average particle size (D50) of 30 μm, and based on 100 wt% of the total powder, it was composed to include 65 wt% urethane, 7 wt% olivine, 3 wt% germanium, 10 wt% apatite, 4 wt% tourmaline, 3 wt% illite, 3 wt% zeolite, 2 wt% silicon dioxide, 0.6 wt% aluminum oxide, 0.6 wt% magnesium oxide, 0.5 wt% calcium oxide, 0.4 wt% iron oxide, 0.3 wt% nickel, 0.3 wt% zirconium, 0.2 wt% cobalt, and 0.1 wt% vanadium.
[0139] Subsequently, a far-infrared emitting patch was manufactured and socks were woven using the same method as in Example 1 above.
[0140] Example 5
[0141] A far-infrared emitting patch was manufactured and a UV-curing coating was applied after attaching the fibers, in the same manner as in Example 1. Subsequently, to increase far-infrared radiation efficiency, a fiber was prepared by mixing terry fabric and brushed fabric in a weight ratio of 1:0.6. Using the mixed fiber, a pile loop structure was formed with a loop length of 3 mm and a velocity of 20 loops / cm. 2 It was formed to have a loop density and 80% porosity. The pile loop structure mix fibers manufactured by the above method were attached to the opposite side of the fiber to which the emission patch was attached to form a heat-radiating layer of the sock.
[0142] Example 6
[0143] A far-infrared emitting patch was manufactured and a UV-curing coating was applied after fiber attachment, in the same manner as in Example 2 above. Subsequently, to increase far-infrared radiation efficiency, a fiber was prepared by mixing terry fabric and brushed fabric in a weight ratio of 1:0.6. Using the mixed fiber, a pile loop structure was formed with a loop length of 3 mm and a velocity of 20 loops / cm. 2 It was formed to have a loop density and 80% porosity. The pile loop structure mix fibers manufactured by the above method were attached to the opposite side of the fiber to which the emission patch was attached to form a heat-radiating layer of the sock.
[0144] Example 7
[0145] A far-infrared emitting patch was manufactured and a UV-curing coating was applied after fiber attachment, in the same manner as in Example 3 above. Subsequently, to increase far-infrared radiation efficiency, a fiber was prepared by mixing terry fabric and brushed fabric in a weight ratio of 1:0.6. Using the mixed fiber, a pile loop structure was formed with a loop length of 3 mm and a velocity of 20 loops / cm. 2It was formed to have a loop density and 80% porosity. The pile loop structure mix fibers manufactured by the above method were attached to the opposite side of the fiber to which the emission patch was attached to form a heat-radiating layer of the sock.
[0146] Example 8
[0147] A far-infrared emitting patch was manufactured and a UV-curing coating was applied after fiber attachment, in the same manner as in Example 4 above. Subsequently, to increase far-infrared radiation efficiency, a fiber was prepared by mixing terry fabric and brushed fabric in a weight ratio of 1:0.6. Using the mixed fiber, a pile loop structure was formed with a loop length of 3 mm and a velocity of 20 loops / cm. 2 It was formed to have a loop density and 80% porosity. The pile loop structure mix fibers manufactured by the above method were attached to the opposite side of the fiber to which the emission patch was attached to form a heat-radiating layer of the sock.
[0148] Comparative Example 1
[0149] Socks were manufactured in the same manner as in Example 1, but only olivine was used as the far-infrared emitting mineral.
[0150] Comparative Example 2
[0151] Socks were manufactured in the same manner as in Example 1, but only germanium was used as the far-infrared emitting mineral.
[0152] Comparative Example 3
[0153] Socks were manufactured in the same manner as in Example 1, but only apatite was used as the far-infrared emitting mineral.
[0154] Experimental Example 1
[0155] Far-infrared radiation and negative ion emissions were measured using the above Examples 1 to 8 and Comparative Examples 1 to 3. Far-infrared radiation emissions were measured using the KFIA-FI-1005 and KFIA-FI-1108 test methods, and negative ion emissions were measured using the KFIA-FI-1042 test method. The measured far-infrared and negative ion emissions are shown in Table 1 below.
[0156] Far-infrared radiation emission amount Anion emission (ION / cc) Emissivity (5~20 μm) Radiant energy (W / m²) 2 ·μm, 37℃) Radiation dose (μSv / hr) Example 1 0.818 3.08X10 2 0.16 584 Example 2 0.855 3.10X10 2 0.04 644 Example 3 0.890 3.28X10 2 0.04 678 Example 4 0.921 3.56X10 2 0.02 716 Example 5 0.824 3.08X10 2 0.16 588 Example 6 0.866 3.12X10 2 0.04 652 Example 7 0.901 3.31X10 2 0.04 684 Example 8 0.923 3.85X10 2 0.02 728 Comparative Example 1 0.782 2.88X10 2 0.28 108 Comparative Example 2 0.778 3.02X10 2 0.25 162 Comparative Example 3 0.768 2.95X10 2 0.28 124
[0157] As shown in Table 1 above, it was confirmed that all of Examples 1 to 8, manufactured according to one embodiment of the present invention, exhibited superior far-infrared radiation and negative ion emission amounts compared to the comparative example. Furthermore, among the examples, the most superior far-infrared radiation and negative ion emission amounts were confirmed in Examples 4 and 8, which include a far-infrared radiation generating mineral, a negative ion generating mineral, and a surface-modified reinforcing agent; among these, the most superior effect was confirmed in Example 8, which formed a double layer through a pile loop structure.
[0158] Experimental Example 2
[0159] The antibacterial and deodorizing effects were confirmed using the above Examples 1 to 8 and Comparative Examples 1 to 3. The antibacterial effect was confirmed by the ASTM E2149 test method, and the deodorizing effect was confirmed by the KCIM-FIR-1004 test method. The confirmed antibacterial and deodorizing effects are shown in Table 2 below (Figs. 5 and 6).
[0160] Antibacterial effect (Staphylococcus, E. coli) Deodorizing effect (120 minutes) 24 hours later 1 week later Example 1 O O 71.5% decrease Example 2 O O 74.6% decrease Example 3 O O 81.3% decrease Example 4 O O 86.8% decrease Example 5 O O 72.0% decrease Example 6 O O 75.2% decrease Example 7 O O 82.4% decrease Example 8 O O 91.4% decrease Comparative Example 1 X X 32.2% decrease Comparative Example 2 X X 24.3% decrease Comparative Example 3 X X 36.2% decrease
[0161] As shown in Table 2 above, it was confirmed that all Examples 1 to 8 prepared according to one embodiment of the present invention exhibited superior antibacterial and deodorizing effects compared to the comparative example. Furthermore, while all examples showed excellent antibacterial effects, the degree of deodorizing effect varied, and the most superior deodorizing effects were confirmed in Examples 4 and 8, which included far-infrared generating minerals, negative ion generating minerals, and surface-modified reinforcing agents. Moreover, among them, the most superior effect was confirmed in Example 8, which formed a double layer through a pile loop structure. Explanation of the symbols
[0162] 100: Functional Socks 110: Far-infrared emitting layer 120: Thermal radiation layer 200: Far-infrared emitting patch
Claims
Claim 1 A step of manufacturing mineral powder by grinding far-infrared emitting minerals and negative ion emitting minerals; a step of manufacturing a mineral mixture by mixing the mineral powder with a binder composition; a step of manufacturing a far-infrared emitting patch by molding the mineral mixture; a step of attaching the far-infrared emitting patch to a fiber surface at intervals of 0.5 to 1.5 cm; and a post-treatment step of UV-curing coating the far-infrared emitting patch attached to the fiber surface. The method includes the step of weaving socks using fibers that have undergone the post-processing step described above, wherein the far-infrared radiating mineral comprises olivine, germanium, and apatite, and the negative ion radiating mineral comprises one or more selected from the group consisting of tourmaline, illite, barley stone, zeolite, and bioceramic, the mineral powder has an average particle size (D50) of 1 to 50 μm, the weight ratio of the mineral powder to the binder composition is 4:6 to 7:3, and the binder composition comprises, based on 100 wt% of the binder composition, 40 to 55 wt% urethane acrylate, 10 to 25 wt% isobornyl acrylate, 5 to 20 wt% hexanediol diacrylate, 5 to 12 wt% ester resin, and terpene phenol A method for manufacturing functional socks characterized by comprising 1 to 8 wt% resin and 2 to 5 wt% photoinitiator. Claim 2 A method for manufacturing functional socks according to claim 1, wherein the far-infrared emitting patch comprises urethane and a far-infrared generating mineral, the far-infrared generating mineral comprises a rare earth element, and the rare earth element comprises a lanthanum (La) element and a yttrium (Y) element. Claim 3 A method for manufacturing functional socks according to claim 1, wherein the far-infrared emitting patch comprises 75-85 wt% urethane, 5-9 wt% olivine, 2-4 wt% germanium, and 8-12 wt% apatite based on 100 wt% of the emitting patch. Claim 4 A method for manufacturing functional socks according to claim 1, wherein the far-infrared emitting patch further comprises a reinforcing agent, wherein the reinforcing agent comprises one or more selected from the group consisting of silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), calcium oxide (CaO), iron oxide (Fe2O3), barium oxide (BaO), lead oxide (PbO), titanium dioxide (TiO2), sodium oxide (NaO2), potassium oxide (K2O), manganese (Mn), chromium (Cr), nickel (Ni), copper (Cu), zirconium (Zr), cobalt (Co), and vanadium (V), and wherein the surface of the reinforcing agent is surface modified with fluoroalkylsilane (FAS) and mercaptosilane. Claim 5 delete Claim 6 delete Claim 7 delete
Citation Information
Patent Citations
Wearing body for human body
JP2007070755A
Sock
KR200297745Y1
Functional socks
KR200433774Y1
Functional socks
KR200496112Y1
Functional socks
KR101176866B1